Microstructures Formation by Fluorocarbon Barrel Plasma Etching. (21st November 2007) - El amrani, A.; Tadjine, R.; Moussa, F. Y.
Abstract : The aim of our study is to generate microstructures in order to improve optical properties of monocrystalline silicon. By mean of fluorocarbon plasma barrel texturing and under certain process conditions, silicon turned black. As a result of silicon surface-plasma particles reactions, porous microstructures are formed, while a longer process time microspikes are developed. These microstructures are responsible of the high level of light trapping on almost the whole range of the usable portion of the solar spectrum. In the wavelength range of 400–1100 nm, the AM1.5G weighted reflection has been reduced to 6.20%. In addition to good trapping, this surface morphology leads to superior absorption, which is about 95% in the 600–1000 nm range and decreases to 36% at 1200 nm. This material is thus less transparent and absorbs near infrared light far more than the untreated silicon. Secondary ion mass spectrometry shows that elements from the ambient gas are deposited or superficially introduced into the silicon. In addition to surface texturing, these impurities are probably the reason of absorptance enhancement. Moreover, a pore formation mechanism is proposed.